Direct medical costs of treatment in newly-diagnosed high-grade glioma among commercially insured US patients. (2nd December 2017) - Jiang, Shan; Hill, Kala; Patel, Dipen; Waldeck, A. Reginald; Botteman, Marc; Aly, Abdalla; Norden, Andrew D.
Abstract: Aim: This analysis assessed the direct medical costs of newly-diagnosed, temozolomide (TMZ)-treated glioblastoma (GBM) from the perspective of a US commercial setting. Materials and methods: The analysis included subjects identified from the IMS PharMetrics LifeLink Plus™ claims database from January 1, 2008 to August 31, 2014 who were ≥18 years of age, had ≥1 malignant brain cancer diagnosis, had brain surgery ≤90 days prior to TMZ initiation, had TMZ treatment, and were continuously enrolled for ≥12 months pre-diagnosis and ≥1 month post-diagnosis. Per-patient per-month (PPPM) and cumulative costs from 3 months pre-diagnosis to various post-diagnosis follow-up time points were calculated. Multivariable analyses were used to estimate adjusted mean cost and identify contributors of cost. Results: The study included 2, 921 subjects (median age = 56 years; 60% male). After diagnosis, the median (interquartile range, IQR) number of inpatient, emergency department, and outpatient visits were 2 (1–4), 1 (1–3), and 19 (13–27); median (IQR) length of stay per hospitalization was 5 (3–9) days. Mean total cumulative costs per patient from 3 months pre-diagnosis to 12 months and to 5 years post-diagnosis were $201, 749 (197, 490–206, 024) and $268, 031 (262, 877–274, 416). Mean (SD) PPPM costs were $818 (1, 128) and $7, 394 (8, 676) pre- and post-GBM diagnosis, respectively. The variables most predictive of cumulative costs included radiation therapy (+$81, 732), ≥2 weeks of hospitalization (+$49, 629), and ≥7 MRI scans (+$40, 105). Conclusions: The direct medical costs of newly-diagnosed, TMZ-treated GBM in commercially insured patients are substantial, with estimated total cumulative costs of $268, 031.